Patients' and Loved Ones' Expectations of Chaplain Services. Issue 3 (3rd July 2022) - Muehlhausen, Beth L.; Foster, Todd; Smith, Aaron H.; Fitchett, George
Abstract: A study assessing the expectations patients and loved ones have of hospital chaplains was conducted at Ascension St. Vincent Indiana hospitals. In-person interviews were conducted with 452 patients and loved ones during an inpatient stay. The survey instrument was a modified version of a survey developed by Dr. Katherine Piderman of the Mayo Clinic. Participants answered questions regarding demographics, awareness of availability, expectations of visits, reasons for wanting to see a chaplain and gave feedback regarding visits if they had seen a chaplain. Results showed that patients and loved ones value chaplains with 93% saying they wanted a chaplain visit. This study was unique in seeking feedback from loved ones as well as patients. It may be equally important to reach out to loved ones during times of crisis when patients themselves are in surgery or sedated and loved ones are experiencing heightened anxiety.